2022
DOI: 10.1039/d1nr08350c
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent flame retardancy of black phosphorus nanosheets

Abstract: Two-dimensional black phosphorus (BP) nanosheets are potential flame-retardant nano-additives. Herein, the effects of the size of BP nanosheets embedded in epoxy resin (EP) on the flame retardancy are studied. BP...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Dry and wet ball milling methods are commonly used mechanical techniques to grind bulk black-P powders into few-layered phosphorene. 212 Zhu et al have developed a solid-state ball milling method to prepare ultrathin black-P nanosheets (Fig. 15a).…”
Section: Synthetic Strategies Of Elemental Phosphorus Materialsmentioning
confidence: 99%
“…Dry and wet ball milling methods are commonly used mechanical techniques to grind bulk black-P powders into few-layered phosphorene. 212 Zhu et al have developed a solid-state ball milling method to prepare ultrathin black-P nanosheets (Fig. 15a).…”
Section: Synthetic Strategies Of Elemental Phosphorus Materialsmentioning
confidence: 99%
“…45,46 In recent years, PR has received great interest in the application for flame-retarded polymeric materials owing to its good compatibility with polymer matrix and facile preparation through mechanical cleavage, liquid ball milling, high-speed shearing, electrochemical exfoliation, and ultrasonic liquid exfoliation. 47 PR has been successfully used for the flame retardancy of epoxy resins, polyurethane, and biodegradable polymers. 48 These studies indicated that the PR nanosheets distributed in flammable polymers can suppress the spread of fire, reduce the release of heat, and decrease the emission of smoke during combustion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Phosphorene (PR) is an emerging 2D nanomaterial with a unique few-layered lamellar nanostructure . It not only has a wide light absorption capability from ultraviolet through visible to near-infrared light thanks to its direct-bandgap semiconductive feature, but also exhibits a highly effective flame-retardant effect on most of organic polymers. , In recent years, PR has received great interest in the application for flame-retarded polymeric materials owing to its good compatibility with polymer matrix and facile preparation through mechanical cleavage, liquid ball milling, high-speed shearing, electrochemical exfoliation, and ultrasonic liquid exfoliation . PR has been successfully used for the flame retardancy of epoxy resins, polyurethane, and biodegradable polymers .…”
Section: Introductionmentioning
confidence: 99%
“…As a novel two-dimensional (2D) semiconductor material, black phosphorus (BP) nanosheets have been widely used in fields such as catalysis, batteries, semiconductors, and sensors . Additionally, similar to other phosphorus-based flame retardants, they can impart excellent flame retardant properties to polymer matrices by trapping radicals in the gas phase and catalyzing char formation in the condensed phase . However, BP still faces the problems of environmental instability (i.e., the lone-pair electrons of P is sensitive to water and oxygen) and poor dispersion in the polymer matrices .…”
Section: Introductionmentioning
confidence: 99%